A fluidized bed catalyst composition and its preparation method and application
By developing a fluidized bed catalyst composition containing copper, alkali metals and rare earth elements, the problem of difficulty in directly oxidizing hydrogen chloride containing high concentrations of fluorine-containing compounds in the prior art is solved, and the durability and industrial application value of the catalyst are realized.
Patent Information
- Application Number
- CN202211662125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-12-23
AI Technical Summary
It is difficult for the prior art to directly use hydrogen chloride containing high concentrations of fluorine-containing compounds to prepare chlorine gas for oxidation, and the catalyst tolerance and industrial application value are insufficient.
A fluidized bed catalyst composition is developed, including catalyst A and catalyst B, both of which contain copper elements, alkali metal elements and rare earth elements, and a catalyst that tolerate high concentrations of fluorine-containing compounds is formed through specific proportions and preparation methods.
The catalyst composition can maintain stable performance during long-term use and can be used in a fluidized bed reactor without defluorination treatment, and has industrial application value.
Smart Images

Figure BDA0004014453240000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, in particular to catalysts used in technical fields related to the oxidation of hydrogen chloride to prepare chlorine, and more particularly to a fluorine-containing compound-resistant hydrogen chloride oxidation fluidized bed catalyst composition and a preparation method thereof. Background Art
[0002] Chlorine is a very important basic chemical raw material, which is widely used in fluorine chemical industry, but the final chlorine resources enter the downstream in the form of by-product hydrogen chloride. It is known that the "closed" cycle of chlorine element achieved by catalytic oxidation of hydrogen chloride is a very green atomic economic reaction system, which has been widely used in the isocyanate industry chain. If it can be applied to the rapidly developing fluorine chemical industry, it will contribute to the sustainable development of fluorine chemical industry and bring extensive social and economic benefits from the perspective of energy conservation and environmental protection.
[0003] However, the by-product hydrogen chloride gas in the production process of organic fluorine chemicals contains a large amount of hydrogen fluoride, fluorinated alkanes, fluorinated olefins, fluorinated aromatics and other compounds. The presence of these compounds will poison the catalyst, which limits its direct application in hydrogen chloride catalyst oxidation technology.
[0004] To solve this problem, the first thing that comes to mind is to purify the fluoride before use, including methods such as chemical precipitation, flocculation precipitation or adsorption. CN201611235574.2 uses a primary calcium chloride solution and a secondary mixed solution of boric acid and potassium chloride to remove HF from HCl gas, but after removal, there is still 2 to 3 ppm of HF in the tail gas. CN201480026738.3 uses a multi-stage tower to eventually reduce the content of chlorodifluoromethane to 0.3 ppm, but the process is complicated and costly.
[0005] Therefore, it is hoped that a technology for preparing chlorine by directly oxidizing hydrogen chloride containing fluorine-containing compounds can be developed, but the difficulty lies in the development of catalysts.
[0006] CN201811588769.4 proposes a process for producing chlorine by one-step oxidation of a mixture of hydrogen chloride and hydrogen fluoride. The process mixture contains 1-15% hydrogen fluoride and 85-99% hydrogen chloride. The reactor adopts a tubular reactor. The reactor material is resistant to hydrogen fluoride corrosion and is one of titanium or titanium alloy, tantalum, and Hastelloy. The ratio of oxygen to hydrogen chloride is 1-3:1, and oxygen is greatly in excess. The high cost of the reactor material and the large amount of oxygen consumption limit its industrial application.
[0007] Based on the above problems, developing an industrially applicable catalyst for the hydrogen chloride oxidation of fluorine-containing compounds to prepare chlorine is one of the technical difficulties that urgently needs to be broken through in this field. Summary of the invention
[0008] In view of the problems existing in the above-mentioned prior art, the present invention provides a fluidized bed catalyst composition and a preparation method thereof. When applied to the preparation of chlorine by oxidation reaction using hydrogen chloride as a raw material, the catalyst composition of the present invention can tolerate a relatively high concentration of fluorine-containing compounds and maintain stable performance during long-term use, and has industrial application value.
[0009] To achieve its purpose, the present invention adopts the following technical solutions:
[0010] In one aspect of the present invention, a fluidized bed catalyst composition is provided, which comprises a catalyst A and a catalyst B, wherein the catalyst A and the catalyst B respectively comprise a carrier and an active component, wherein:
[0011] The active components of catalyst A include copper, alkali metal and rare earth elements;
[0012] The carrier of catalyst B is alumina, and the active components include copper, alkali metal and rare earth elements;
[0013] It is understood by those skilled in the art that, although both Catalyst A and Catalyst B contain alkali metal elements and rare earth elements, the specific alkali metal elements and rare earth elements contained in the two catalysts may be the same or different.
[0014] By weight, the rare earth element content of the catalyst B is 1.1-20 times the rare earth element content of the catalyst A, preferably 1.2-15 times, for example, 1.5 times, 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, 5 times, 5.5 times, 6 times, 6.5 times, 7 times, 7.5 times, 8 times, 8.5 times, 9 times, 9.5 times, 10 times, 10.5 times, 11 times, 11.5 times, 12 times, 12.5 times, 13 times, 13.5 times, 14 times, 14.5 times, 15 times, 15.5 times, 16 times, 16.5 times, 17 times, 17.5 times, 18 times, 18.5 times, 19 times, 19.5 times, etc.;
[0015] The weight ratio of the catalyst A to the catalyst B is 1-100:1, for example, 4:1, 8:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, etc.
[0016] In a preferred embodiment of the present invention, in the catalyst A, the copper element content is 4-10wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and the like; the alkali metal element content is 1-10wt%, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and the like; the rare earth element content is 2-20wt%, for example, 5wt%, 10wt%, 15wt% and the like.
[0017] In a preferred embodiment of the present invention, in the catalyst B, the copper element content is 0.1-10wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and the like; the alkali metal element content is 0.1-10wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and the like; the rare earth element content is 2-40wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% and the like.
[0018] In a preferred embodiment of the present invention, the carrier of the catalyst A is one or more of alumina, molecular sieve and titanium oxide.
[0019] In a preferred embodiment of the present invention, the alkali metal element is selected from one or both of potassium and sodium.
[0020] In a preferred embodiment of the present invention, the rare earth element is selected from one or more of cerium, lanthanum, praseodymium, neodymium and samarium.
[0021] In a preferred embodiment of the present invention, the catalyst A and catalyst B independently further contain 0-10wt% of other metal elements, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and the like of other metal elements; the other metal elements of the catalyst A and catalyst B are independently selected from one or more of magnesium, calcium, barium, manganese, iron, nickel, cobalt, zinc, ruthenium and titanium.
[0022] In a preferred embodiment of the present invention, the copper content of the catalyst B is less than the copper content of the catalyst A.
[0023] In a preferred embodiment of the present invention, the attrition index of the catalyst A and the catalyst B is independently <3%, preferably <2%.
[0024] In a preferred embodiment of the present invention, the average particle size of the catalyst A and the catalyst B is independently 40-80 μm, such as 50 μm, 60 μm, 70 μm, etc.
[0025] In another aspect of the present invention, it relates to a method for preparing the above-mentioned catalyst composition, which comprises uniformly mixing catalyst A and catalyst B to prepare the catalyst composition, wherein the preparation of catalyst A and catalyst B independently comprises the following steps:
[0026] (1) adding the carrier to a solution of a compound containing an active ingredient and stirring to obtain a paste;
[0027] (2) subjecting the paste to centrifugal spray drying to obtain a dry mix;
[0028] (3) calcining the dry mixture to obtain a catalyst.
[0029] In the catalyst preparation method of the present invention, step (1) involves the use of a solution of a compound containing an active component. In the technical field of the present invention, when the active component of the catalyst is determined, the technician can appropriately select the compound containing the active component and obtain a mixed solution of the compound containing these active components in a suitable manner. The compound containing the active component is, for example, a salt containing these active components, such as nitrates and chlorides.
[0030] In a preferred embodiment of the present invention, the carrier in step (1) is a wet carrier, and the preparation method is: disperse the solid carrier in water, add a liquid carrier precursor; according to the added carrier, the technician can appropriately select the liquid carrier precursor, for example, when the carrier is aluminum oxide, the liquid carrier precursor can be selected as aluminum sol; stir evenly to obtain the wet carrier. According to the prepared wet carrier, the technician can appropriately add acid, such as nitric acid or hydrochloric acid, after stirring evenly, and the technician can also appropriately select the amount of acid added, for example, to make the pH of the wet carrier ≤5, to obtain the wet carrier.
[0031] In a preferred embodiment of the present invention, the stirring time in step (1) is 0.1-20 h, such as 1 h, 5 h, 10 h, 15 h, etc.
[0032] In a preferred embodiment of the present invention, the outlet temperature of the centrifugal spray drying in step (2) is 90-150°C, such as 100°C, 120°C, 140°C, etc.
[0033] In a preferred embodiment of the present invention, the calcination temperature in step (3) is 450-650°C, such as 500°C, 550°C, 600°C, etc.; the calcination time is 1-6h, such as 2h, 3h, 4h, 5h, etc.
[0034] In another aspect of the present invention, it relates to a method for preparing chlorine by oxidation reaction using hydrogen chloride as a raw material in the presence of a catalyst, wherein the catalyst is the above-mentioned catalyst composition or the catalyst composition obtained by the above-mentioned preparation method.
[0035] In a preferred embodiment of the present invention, the oxidation reaction is carried out in a fluidized bed reactor. During the reaction, the maximum temperature in the fluidized bed reactor is controlled to be 320-430°C, preferably 340-420°C; the mass space velocity of hydrogen chloride is 0.05-1.5h -1 ; The molar ratio of hydrogen chloride to oxygen is 1-4:1; the reaction pressure is 0.1-1.0Mpa.
[0036] In a preferred embodiment of the present invention, the raw material further contains a fluorine-containing compound. Preferably, the concentration of the fluorine-containing compound in the raw material is 0.1-100 mg / m 3 The fluorine-containing compound described in the present invention refers to a substance containing fluorine element present in the hydrogen chloride raw material, such as hydrogen fluoride, fluorine-containing alkanes, fluorine-containing olefins and fluorine-containing aromatic hydrocarbons.
[0037] It is known that common metal oxides have a certain ability to adsorb fluorine. However, ordinary fluorine-containing compound adsorbents are inert in the hydrogen chloride oxidation reaction. Either the initial strength is low, or the fluorine-containing compound cannot reduce its strength and is gradually removed from the reactor, or it cannot be selectively adsorbed, resulting in a decrease in the strength of the main catalyst A, and is therefore not suitable for a fluidized bed system.
[0038] The inventors surprisingly found that in the system of hydrogen chloride oxidation to produce chlorine, in the catalyst composition of the present invention, the catalyst with a relatively higher rare earth metal content is more conducive to the adsorption of fluorine, and after the catalyst adsorbs fluorine, its strength gradually decreases. When two catalysts with different rare earth contents are mixed, fluorine is more likely to be preferentially adsorbed on the catalyst with a higher rare earth content, and its mechanical strength decreases faster than that of the catalyst with a lower rare earth content.
[0039] When the catalyst composition of the present invention is applied to a fluidized bed reactor, during the actual operation, the catalyst A and the catalyst B can be effectively mixed and uniform, wherein the catalyst A is the main catalytically active component, which is used to catalyze the reaction of hydrogen chloride oxidation to produce chlorine, and the catalyst B is a secondary catalytically active component, but as the main component for adsorbing fluorine-containing compounds. After the fluorine-containing compounds are adsorbed on the catalyst B, as the reaction time is extended, the strength of the catalyst B will gradually decrease and it will be more easily worn out. The catalyst A will have less loss during long-term operation due to the low fluorine content. In order to maintain the integrity of the catalyst composition, the catalyst composition can be supplemented regularly, but the proportion of the catalyst B in the supplemented catalyst composition can be slightly higher than that in the reactor. After the selective adsorption of the fluorine-containing compound, the catalyst B will gradually wear out due to the reduced strength, and thus be taken out of the reactor, and can be gradually supplemented during continuous operation to keep the catalyst composition in the reaction system basically stable.
[0040] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in that the fluidized bed catalyst composition provided by the present invention can be directly used in a fluidized bed reactor to catalyze the oxidation of hydrogen chloride to prepare chlorine without defluorination treatment on the basis of a high concentration of fluorine-containing compounds in the hydrogen chloride raw gas, and the catalyst does not show obvious activity decline after long-term use, and has industrial application value. DETAILED DESCRIPTION
[0041] The present invention is described in further detail below, but the present invention is not limited thereby.
[0042] raw material
[0043] The metal salt raw materials used in the examples or comparative examples were purchased from Xilong Chemical Co., Ltd., alumina powder was purchased from Zibo Chaoke Alumina Material Co., Ltd., pseudoboehmite was purchased from Shandong Aluminum Co., Ltd., and aluminum sol was purchased from Zibo Jinqi Chemical Technology Co., Ltd. Unless otherwise specified, other raw materials appearing in this article are conventional commercially available raw materials.
[0044] Test Method
[0045] 1. Test method for hydrogen chloride conversion rate:
[0046] During the catalyst reaction performance test, samples were taken three times every 24 hours for analysis, and the average conversion rate of the entire operation process was taken as the conversion rate of the catalyst.
[0047] The test method for any single hydrogen chloride conversion rate is as follows:
[0048] (1) Detection principle
[0049] Cl2+2KI=2KCl+I2
[0050] I2+2Na2S2O3=2NaI+Na2S4O6
[0051] HCl+NaOH=NaCl+H2O
[0052] (2) Preparation and calibration of 0.1 mol / L Na2S2O3 solution
[0053] Weigh about 6.2g of Na2S2O3·5H2O, dissolve it in an appropriate amount of freshly boiled and cooled distilled water (to remove O2 and CO2 in the water), add 0.05-0.1g of Na2CO3 (to inhibit microbial growth), make up 250mL solution, and store it in a brown bottle in a dark place; calibrate it after 2 weeks.
[0054] Accurately weigh 0.15g of K2Cr2O7 (dried at 110℃ for 2h) in an iodine volumetric flask, add 20mL of water to dissolve, add 2g of KI and 10mL of H2SO4 with a mass concentration of 1wt%, shake well and let stand for 5 minutes, then add 50mL of water to dilute, and titrate with Na2S2O3 solution until the solution turns light yellow-green. Add 2mL of starch indicator and continue titrating with Na2S2O3 solution until the solution turns from blue to light green (the end point is Cr 3+ The calibration was performed three times in parallel and the average value was taken.
[0055] (3) Analysis and testing process
[0056] a) Sampling: Replace the 250mL sampling bottle with the sample gas to be tested for 3 minutes (gas enters from the bottom and exits from the top), ensuring that there are no impurities in the sampling bottle. The sample gas in the sampling bottle is fully reacted with a 15wt% KI aqueous solution. The Cl2 in the sample gas reacts with KI to generate I2 (in the form of I3 - The HCl is dissolved in the absorption liquid in the form of HCl. If I2 precipitation occurs, it will easily lead to poor accuracy of the results and resampling is required. HCl is absorbed to form a hydrochloric acid aqueous solution. Then titrate.
[0057] b) I2(I3 - ) titration: Take out 25.00mL of absorption solution into a 250mL conical flask, dilute with 50mL of distilled water, and titrate with the prepared and calibrated Na2S2O3 solution until it turns light yellow. Add 2mL of starch solution and continue titrating until the blue color just disappears, which is the end point. Record the volume of Na2S2O3 solution consumed in the titration, and you can calculate the I2(I3 - ) content, and then calculate the amount of Cl2 in the sample gas to be tested.
[0058] c) Titration of hydrochloric acid in the absorption liquid: Add 2-3 drops of phenolphthalein reagent to the sample that has been titrated in step b). The colorless liquid turns red, and the red does not change color within half a minute (if it does not turn from colorless to red, it means that there is no hydrochloric acid in the absorption liquid, provided that the experimental process is correct). Then titrate with the prepared and calibrated NaOH standard solution until it becomes colorless, which is the titration end point. Record the volume of NaOH standard solution consumed in the titration, and you can calculate the H in the absorption liquid. + The content of HCl in the sample gas to be tested can be calculated.
[0059] (4) Calculate the conversion rate of hydrogen chloride in the sample Conv:
[0060]
[0061] in:
[0062] a represents the concentration of Na2S2O3 solution, mol / L;
[0063] b represents the volume of Na2S2O3 solution consumed in titration, mL;
[0064] c represents the concentration of NaOH standard solution, mol / L;
[0065] d represents the volume of NaOH standard solution consumed in titration, mL.
[0066] 2. Test method for catalyst wear index (straight tube method):
[0067] The wear index was determined according to the method in the standard “Straight tube method for determination of wear index of catalytic cracking catalyst” Q / TSH3490909 2006.
[0068] 3. Test method for catalyst particle size distribution:
[0069] The particle size was measured using Dandong Bettersize 2000LD laser particle size analyzer, and the dispersant was deionized water.
[0070] VMD: volume mean diameter; unless otherwise specified, the average particle size of the catalyst mentioned in the present invention refers to the volume mean diameter.
[0071] 4. Test method for catalyst slurry viscosity
[0072] The Shanghai Changji NDJ-1B rotational viscometer was used for the measurement. The No. 3 rotor was selected and the rotation speed was 60 rpm.
[0073] 5. Determination of active component content in catalyst:
[0074] The content of active component elements in the catalyst was determined using an Agilent 5110 ICP-OES instrument.
[0075] Example
[0076] Example 1
[0077] (1) Preparation of catalyst composition
[0078] Preparation of wet carrier: Weigh 280g of pseudo-boehmite and disperse it in 400g of water, add 630g of aluminum sol with a solid content of 30wt% under stirring, and stir evenly to obtain a wet carrier.
[0079] Preparation of catalyst A: 80 g of copper chloride, 150 g of neodymium nitrate, 30 g of potassium chloride, 10 g of magnesium chloride, and 10 g of a 50 wt% manganese nitrate aqueous solution were weighed and dissolved in 400 mL of distilled water to obtain a mixed solution. The wet carrier prepared above was added during stirring, and stirring was continued for 1 hour to obtain a paste with a viscosity of 6200 mPa·s; a dry mixture was obtained after centrifugal spray drying at an outlet temperature of 101° C.; and then calcined at 600° C. for 5 hours to obtain a catalyst product.
[0080] After analysis, the catalyst has a copper content of 5.2wt%, a neodymium content of 8.7wt%, a potassium content of 2.8wt%, a magnesium content of 0.45wt%, and a manganese content of 0.27wt%; an average particle size of 67.1μm; and a wear index of 1.27%.
[0081] Preparation of Catalyst B: 34 g of copper chloride, 300 g of cerium nitrate, 30 g of potassium chloride, 10 g of magnesium chloride, and 10 g of a 50 wt% aqueous solution of manganese nitrate were weighed and dissolved in 400 mL of distilled water to obtain a mixed solution. The wet carrier prepared above was added during stirring, and stirring was continued for 1 hour to obtain a paste with a viscosity of 4900 mPa·s; a dry mixture was obtained after centrifugal spray drying at an outlet temperature of 115°C; and then calcined at 600°C for 5 hours to obtain a catalyst product.
[0082] After analysis, the copper content of the catalyst is 2.2wt%, the cerium content is 16.6wt%, the potassium content is 2.7wt%, the magnesium content is 0.44wt%, and the manganese content is 0.26wt%; the average particle size of the catalyst is 66.8μm; and the wear index is 0.98%.
[0083] 800 g of the catalyst A and 200 g of the catalyst B were weighed and mixed evenly to prepare a catalyst composition.
[0084] (2) Catalyst performance test:
[0085] The above catalyst composition was placed in a fluidized bed reactor with an inner diameter of 30 mm and a height of 700 mm.3 Hydrogen chloride gas of hydrogen fluoride is used as raw material, and the molar hydrogen chloride / oxygen ratio is controlled to be 2 / 1; when the mass space velocity of hydrogen chloride is 0.39h -1 , the reaction temperature is 390-400°C, and the reaction pressure is 0.3MPa (absolute pressure) under the conditions of hydrogen chloride oxidation to produce chlorine. After 100 hours of continuous reaction, the conversion rate of hydrogen chloride is tested to be 84%, and the conversion rate of hydrogen chloride after 3000 hours of continuous reaction under this condition is 85.2%. No catalyst is added during the period, and no obvious hydrogen fluoride is detected in the reaction tail gas. The catalyst is disassembled to obtain about 962g of the main catalyst and about 74g of fine powder. XRF (X-ray fluorescence spectrometry, using PANalytical Epsilon 3, the same below) characterization is performed on it. The fluorine content on the main catalyst is 2.4wt%, and the fluorine content in the fine powder is about 17.3wt%. EDX (energy dispersive X-ray spectrometry, using Hitachi S-4800 scanning electron microscope, the same below) analysis found that the fluorine on the main catalyst is mainly present in catalyst B.
[0086] Example 2
[0087] (1) Preparation of catalyst composition
[0088] Preparation of Catalyst A: The same as Example 1, except that 130 g of copper nitrate, 90 g of lanthanum nitrate, 90 g of cerium nitrate, 70 g of potassium chloride, and 10 g of a 50 wt% manganese nitrate aqueous solution were used to prepare the catalyst.
[0089] After analysis, the catalyst has a copper content of 6.0wt%, a potassium content of 6.4wt%, a cerium content of 5.1wt%, a lanthanum content of 5.0wt%, and a manganese content of 0.27wt%; an average particle size of 55.1μm; and a wear index of 0.73%.
[0090] Preparation of Catalyst B: The same as Example 1, except that 9 g of copper chloride, 300 g of cerium nitrate, 165 g of samarium nitrate, and 21 g of potassium chloride were used to prepare the catalyst.
[0091] After analysis, the catalyst has a copper content of 0.55wt%, a potassium content of 1.8wt%, a cerium content of 16.1wt%, and a samarium content of 9.3wt%; an average particle size of 56.3μm; and a wear index of 0.79%.
[0092] 600 g of the catalyst A and 400 g of the catalyst B were weighed and mixed evenly to prepare a catalyst composition.
[0093] (2) Catalyst performance test:
[0094] Same as Example 1.
[0095] After 100 hours of continuous reaction, the conversion rate of hydrogen chloride was tested to be 81.9%. After 3000 hours of continuous reaction under this condition, the conversion rate of hydrogen chloride was 83.7%. No catalyst was added during the reaction, and no obvious hydrogen fluoride was detected in the reaction tail gas. The catalyst was disassembled to obtain about 958g of main catalyst and about 85g of fine powder. XRF characterization was performed on them. The fluorine content on the main catalyst was 1.9wt%, and the fluorine content in the fine powder was about 21wt%. EDX analysis found that the fluorine on the main catalyst was mainly present in catalyst B.
[0096] Example 3
[0097] (1) Preparation of catalyst composition
[0098] Preparation of Catalyst A: The same as Example 1, except that 100g of alumina powder, 80g of HY molecular sieve and 700g of aluminum sol with a solid content of 30wt% are used to prepare the wet carrier; 130g of copper chloride, 42g of neodymium nitrate, 55g of potassium chloride, 10g of magnesium chloride and 60g of ferric nitrate are used to prepare the catalyst.
[0099] After analysis, the catalyst contains 7.9wt% copper, 2.3wt% neodymium, 4.7wt% potassium, 0.42wt% magnesium and 1.4wt% iron; the average particle size is 74.5μm; and the wear index is 1.89%.
[0100] Preparation of Catalyst B: The same as Example 1, except that 3 g of copper chloride, 400 g of cerium nitrate, 300 g of lanthanum nitrate and 3 g of potassium chloride were used to prepare the catalyst.
[0101] After analysis, the catalyst has a copper content of 0.17wt%, a potassium content of 0.24wt%, a cerium content of 19.4wt%, and a lanthanum content of 14.4wt%; an average particle size of 72.6μm; and an abrasion index of 2.02%.
[0102] 900 g of the catalyst A and 100 g of the catalyst B were weighed and mixed evenly to prepare a catalyst composition.
[0103] (2) Catalyst performance test:
[0104] Same as Example 1.
[0105] After 100 hours of continuous reaction, the conversion rate of hydrogen chloride was 83.3%. After 3000 hours of continuous reaction under this condition, the conversion rate of hydrogen chloride was 82.6%. No catalyst was added during the reaction, and no obvious hydrogen fluoride was detected in the reaction tail gas. The catalyst was disassembled to obtain about 928g of the main catalyst and about 108g of fine powder. XRF characterization showed that the fluorine content on the catalyst was 1.01wt%, and the fluorine content in the fine powder was 24.6wt%. EDX analysis found that the content of catalyst B in the main catalyst was relatively low.
[0106] 72g of catalyst B was added to the main catalyst that had been reacting for 3000h and mixed evenly, and the reaction was continued for 3000h. The conversion rate of hydrogen chloride was 83.1%. No catalyst was added during the reaction, and no obvious hydrogen fluoride was detected in the reaction tail gas. The catalyst was disassembled to obtain about 944g of the main catalyst and about 92g of fine powder. XRF characterization showed that the fluorine content on the main catalyst was 1.99wt%, and the fluorine content in the fine powder was 28.8wt%. EDX analysis found that the content of catalyst B in the main catalyst was reduced.
[0107] Comparative Example 1
[0108] (1) Preparation of catalyst composition
[0109] 1000 g of catalyst A prepared in Example 1 was weighed as the catalyst for the following performance test, without using catalyst B.
[0110] (2) Catalyst performance test:
[0111] Same as Example 1.
[0112] After 100 hours of continuous reaction, the conversion rate of hydrogen chloride was 84.2%. After 3000 hours of continuous reaction under this condition, the conversion rate of hydrogen chloride was 63.1%. No catalyst was added during this period. The concentration of hydrogen fluoride in the reaction tail gas gradually increased from the initial undetectable to about 11 mg / m 3 The catalyst was disassembled to obtain about 779g of main catalyst and about 257g of fine powder. XRF characterization showed that the fluorine content on the main catalyst was 3.1wt%, and the fluorine content in the fine powder was about 4.6wt%. Due to the adsorption of fluorine, the catalyst strength was significantly reduced, a large amount of fine powder was generated, and the performance of the main catalyst was significantly reduced.
[0113] Comparative Example 2
[0114] (1) Preparation of catalyst composition
[0115] Preparation of Catalyst B:
[0116] Preparation of wet carrier: Same as Example 1.
[0117] 34g of copper chloride, 100g of cerium nitrate, 30g of potassium chloride, 10g of magnesium chloride, and 10g of 50wt% manganese nitrate aqueous solution were weighed and dissolved in 400mL of distilled water to obtain a mixed solution. The wet carrier prepared above was added during stirring. After stirring for 1h, a paste with a viscosity of 5040mPa·s was obtained. The dry mixture was centrifugally spray-dried at an outlet temperature of 115°C. The catalyst product was then calcined at 600°C for 5h. After analysis, the catalyst had a copper content of 2.5wt%, a cerium content of 6.4wt%, a potassium content of 3.1wt%, a magnesium content of 0.51wt%, and a manganese content of 0.30wt%. The average particle size was 64.8μm, and the wear index was 1.79%.
[0118] 800 g of the catalyst A prepared in Example 1 and 200 g of the above catalyst B were weighed and mixed evenly to form a catalyst composition.
[0119] (2) Catalyst performance test:
[0120] Same as Example 1.
[0121] After 100 hours of continuous reaction, the conversion rate of hydrogen chloride was 82.6%. After 3000 hours of continuous reaction under this condition, the conversion rate of HCl was 59.7%. No catalyst was added during the reaction. The concentration of hydrogen fluoride in the reaction tail gas gradually increased from the initial undetectable to about 18 mg / m 3 The catalyst was disassembled to obtain about 751g of main catalyst and about 285g of fine powder. XRF characterization showed that the fluorine content on the main catalyst was 3.2wt%, and the fluorine content in the fine powder was about 4.2wt%. Due to the adsorption of fluorine, the catalyst strength was significantly reduced, resulting in a large amount of fine powder, and the performance of the main catalyst was significantly reduced.
[0122] Although the present invention has been described in detail for the purpose of illustration in the foregoing text, it should be understood that these detailed descriptions are only for illustration and can be modified by those skilled in the art without departing from the spirit and scope of the present invention. The present invention is limited only by the claims.
Claims
1. A fluidized bed catalyst composition, comprising a catalyst A and a catalyst B, wherein the catalyst A and the catalyst B respectively comprise a carrier and an active component, wherein: The active components of catalyst A include copper, alkali metal and rare earth elements; The carrier of catalyst B is alumina, and the active components include copper, alkali metal and rare earth elements; The rare earth element content of the catalyst B is 1.5-20 times the rare earth element content of the catalyst A by weight; The weight ratio of the catalyst A to the catalyst B is 1-100:
1.
2. The catalyst composition according to claim 1, wherein The rare earth element content of the catalyst B is 1.5-15 times the rare earth element content of the catalyst A.
3. The catalyst composition according to claim 1, wherein In the catalyst A, the copper content is 4-10wt%, the alkali metal content is 1-10wt%, and the rare earth element content is 2-20wt%; and / or In the catalyst B, the content of copper element is 0.1-10wt%, the content of alkali metal element is 0.1-10wt%, and the content of rare earth element is 5-40wt%.
4. The catalyst composition according to claim 1, wherein The carrier of the catalyst A is one or more of alumina, molecular sieve and titanium oxide; and / or The alkali metal element is selected from one or both of potassium and sodium; and / or The rare earth element is selected from one or more of cerium, lanthanum, praseodymium, neodymium and samarium.
5. The catalyst composition according to any one of claims 1 to 4, wherein The catalyst A and catalyst B independently further contain 0-10 wt% of other metal elements, and the other metal elements of the catalyst A and catalyst B are independently selected from one or more of magnesium, calcium, barium, manganese, iron, nickel, cobalt, zinc, ruthenium and titanium.
6. The catalyst composition according to any one of claims 1 to 4, wherein The copper content of the catalyst B is less than the copper content of the catalyst A; and / or The attrition index of the catalyst A and the catalyst B is independently <3%; and / or The average particle diameters of the catalyst A and the catalyst B are independently 40-80 μm.
7. A method for preparing a catalyst composition according to any one of claims 1 to 6, comprising uniformly mixing catalyst A and catalyst B to prepare a catalyst composition, wherein: The preparation of catalyst A and catalyst B independently comprises the following steps: (1) adding the carrier to a solution of a compound containing an active ingredient and stirring to obtain a paste; (2) subjecting the paste to centrifugal spray drying to obtain a dry mix; (3) calcining the dry mixture to obtain a catalyst.
8. The preparation method according to claim 7, wherein: The carrier in step (1) is a wet carrier, and the preparation method is: disperse the solid carrier in water, add the liquid carrier precursor, and stir evenly to obtain the wet carrier.
9. The preparation method according to claim 7 or 8, wherein: The stirring time in step (1) is 0.1-20h; and / or The outlet temperature of the centrifugal spray drying in step (2) is 90-150° C.; and / or In step (3), the calcination temperature is 450-650° C. and the calcination time is 1-6 hours.
10. A method for preparing chlorine by oxidation reaction using hydrogen chloride as a raw material in the presence of a catalyst, wherein: The catalyst is the catalyst composition according to any one of claims 1 to 6 or the catalyst composition obtained by the preparation method according to any one of claims 7 to 9.
11. The method according to claim 10, wherein: The oxidation reaction is carried out in a fluidized bed reactor. During the reaction, the maximum temperature in the fluidized bed reactor is controlled to be 320-430°C; the mass space velocity of hydrogen chloride is 0.05-1.5h -1 ; The molar ratio of hydrogen chloride to oxygen is 1-4:1; The reaction pressure is 0.1-1.0MPa; and / or The raw material also contains a fluorine-containing compound.
12. The method according to claim 11, wherein: The concentration of the fluorine-containing compound in the raw material is 0.1-100 mg / m 3 .
Citation Information
Patent Citations
Method for purifying hydrogen chloride
CN105377751A
Method for removing hydrogen fluoride gas in hydrogen chloride gas
CN106744688A
A process for producing chlorine gas by one-step oxidation of a mixture of hydrogen chloride and hydrogen fluoride.
CN109607478B
Catalyst applied to hydrogen chloride oxidization to prepare chlorine as well as preparation method and application thereof
CN108097232A
Catalyst for oxidization of hydrogen chloride to prepare chlorine, and preparation method and application thereof
CN111167468A
Cited By
Method for pretreating Fischer-Tropsch synthesis catalyst
CN120094583A